Advances in library administration and organization. Vol. 31 - Williams, Delmus Eugene; Golden, Janine (Advances in library administration and organization,, 2012)
The work of a librarian can be transformational. The role of the dynamic librarian involves thinking of change management as an integral part of the way that libraries are expanding to include unexpected challenges, services that might not be considered part of their portfolio and approaches to their work that are anything but traditional. The articles in this volume of Advances in Library Administration and Organization attest to that commitment to understand the process of change. The book will examine the challenges that working administrators face and discusses how to enable them to look more closely at their operations and to reconsider how to develop people and the organizations in which they work. As in previous volumes of Advances in Library Administration and Organization, the studies outlined in the chapters of Volume 31 will provide strategies that will be of value in addressing challenges faced by current and future library managers.